2022
DOI: 10.1200/po.21.00330
|View full text |Cite
|
Sign up to set email alerts
|

ERBB2 Copy Number as a Quantitative Biomarker for Real-World Outcomes to Anti–Human Epidermal Growth Factor Receptor 2 Therapy in Advanced Gastroesophageal Adenocarcinoma

Abstract: PURPOSE Human epidermal growth factor receptor 2 (HER2) overexpression or amplification ( ERBB2amp) are biomarkers for approved anti-HER2 therapies. ERBB2amp may better predict response compared with immunohistochemistry or in situ hybridization, and quantitative copy number (CN) may further stratify patients. We characterized ERBB2amp in advanced gastroesophageal adenocarcinomas (GEA) and hypothesized that increased CN was associated with better outcome to trastuzumab. METHODS Comprehensive genomic profiling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…ERBB2 CN as a continuous value showed a significant association with PFS in this study, as well as in two recent studies using the nationwide (US-based) deidentified Flartiron Health-Foundation clinic genomic database and Foundation Medicine genomic database for gastroesophageal adenocarcinoma. 7,13 The former study demonstrated significant differences in the time to trastuzumab discontinuation and OS between patients with HER2 concordance (HER2+ and ERBB2 amplification+) and those with discordance (HER2+ and ERBB2 amplification-) and between patients with high ERBB2 CN (≥ median value, 25) and those with low ERBB2 CN. 7 The latter showed that the association of ERBB2 CN with PFS was not observed in HER2-positive patients who were treated with chemotherapy without trastuzumab.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…ERBB2 CN as a continuous value showed a significant association with PFS in this study, as well as in two recent studies using the nationwide (US-based) deidentified Flartiron Health-Foundation clinic genomic database and Foundation Medicine genomic database for gastroesophageal adenocarcinoma. 7,13 The former study demonstrated significant differences in the time to trastuzumab discontinuation and OS between patients with HER2 concordance (HER2+ and ERBB2 amplification+) and those with discordance (HER2+ and ERBB2 amplification-) and between patients with high ERBB2 CN (≥ median value, 25) and those with low ERBB2 CN. 7 The latter showed that the association of ERBB2 CN with PFS was not observed in HER2-positive patients who were treated with chemotherapy without trastuzumab.…”
Section: Discussionmentioning
confidence: 96%
“… 7 The latter showed that the association of ERBB2 CN with PFS was not observed in HER2-positive patients who were treated with chemotherapy without trastuzumab. 13 Taken together, ERBB2 CN is a robust efficacy predictor of trastuzumab treatment in patients with HER2-positive AGC. Setting a common optimal cutoff value for ERBB2 CN seemed to be difficult, because the trastuzumab effect continuously emerged as the ERBB2 CN increased, and the NGS methods differed across studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…From a translational perspective, retrospective studies showed the impact of HER2 "hyperamplification" (i.e. higher HER2 CNV or its values greater than a specific cut-off) on better outcomes of trastuzumab or even long-term response in patients with HER2-positive metastatic GC/GEJC, since higher level of HER2 amplification assessed by ISH or NGS may be a surrogate of HER2 addiction [8,9,[14][15][16]. Also, patients with higher amounts of HER2 in their tumors assessed by IHC or mass spectrometry derive greater benefit from trastuzumab-based therapy [1,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term benefit from trastuzumab-based first-line therapy is observed in a minority (about 15%) of patients and the potential biological explanations are multiple. First, research showed that higher HER2 copy number variation (CNV) in tumor cells is associated with superior outcomes after HER2 targeting treatments [8,9], since HER2 "hyper-amplification" may be a surrogate of HER2 addiction and is clearly associated with long-term responses to trastuzumab. Similar results have been reported for HER2 overexpression assessed by immunohistochemistry (IHC) or mass spectrometry [1,10,11].…”
Section: Introductionmentioning
confidence: 99%